Gualberto Valverde, Rebeca (2021). Wasteland Modernism: The Disenchantment of Myth. Valencia: Publicacions de la Universitat de València. - de la Parra Fernández, Laura (Complutense Journal of English Studies, 2021)
Book review of Gualberto Valverde, Rebeca (2021). Wasteland Modernism: The Disenchantment of Myth. Valencia: Publicacions de la Universitat de València.